Imaging Brain Deoxyglucose Uptake and Metabolism by Glucocest MRI. Issue 8 (August 2013) - Nasrallah, Fatima A; Pagès, Guilhem; Kuchel, Philip W; Golay, Xavier; Chuang, Kai-Hsiang
2-Deoxy-D-glucose (2DG) is a known surrogate molecule that is useful for inferring glucose uptake and metabolism. Although 13 C-labeled 2DG can be detected by nuclear magnetic resonance (NMR), its low sensitivity for detection prohibits imaging to be performed. Using chemical exchange saturation transfer (CEST) as a signal-amplification mechanism, 2DG and the phosphorylated 2DG-6-phosphate (2DG6P) can be indirectly detected in 1 H magnetic resonance imaging (MRI). We showed that the CEST signal changed with 2DG concentration, and was reduced by suppressing cerebral metabolism with increased general anesthetic. The signal changes were not affected by cerebral or plasma pH, and were not correlated with altered cerebral blood flow as demonstrated by hypercapnia; neither were they related to the extracellular glucose amounts as compared with injection of D- and L-glucose. In vivo 31 P NMR revealed similar changes in 2DG6P concentration, suggesting that the CEST signal reflected the rate of glucose assimilation. This method provides a new way to use widely available MRI techniques to image deoxyglucose/glucose uptake and metabolism in vivo without the need for isotopic labeling of the molecules.